Anticancer and antibacterial potential of robust Ruthenium(II) arene complexes regulated by choice of α-diimine and halide ligands. (1st August 2021) - Zanda, Emanuele; Busto, Natalia; Biancalana, Lorenzo; Zacchini, Stefano; Biver, Tarita; Garcia, Begoña; Marchetti, Fabio
Abstract: Several complexes of general formula [Ru(halide)(η 6 - p -cymene)(α-diimine)] +, in the form of nitrate, triflate and hexafluorophosphate salts, including a newly synthesized iodide compound, were investigated as potential anticancer drugs and bactericides. NMR and UV–Vis studies evidenced remarkable stability of the complexes in water and cell culture medium. In general, the complexes displayed strong cytotoxicity against A2780 and A549 cancer cell lines with IC50 values in the low micromolar range, and one complex (RUCYN ) emerged as the most promising one, with a significant selectivity compared to the non-cancerous HEK293 cell line. A variable affinity of the complexes for BSA and DNA binding was ascertained by spectrophotometry/fluorimetry, circular dichroism, electrophoresis and viscometry. The performance of RUCYN appears associated to enhanced cell internalization, favored by two cyclohexyl substituents, rather than to specific interaction with the evaluated biomolecules. The chloride/iodide replacement, in one case, led to increased cellular uptake and cytotoxicity at the expense of selectivity, and tuned DNA binding towards intercalation. Complexes with iodide or a valproate bioactive fragment exhibited the best antimicrobial profiles. Graphical abstract: Emanuele Zanda, Natalia Busto, Lorenzo Biancalana, Stefano Zacchini, Tarita Biver, Begoña Garcia, Fabio MarchettiWithin cationic Ru  + II -arene complexes, the appropriate choice of halide and substituents on α -diimine allows a fine modulation of cytotoxicity, interaction with biomolecules and antibacterial activity, and RUCYN (nitrate salt) emerged as the most promising anticancer candidate. Image 1 Highlights: Cytotoxicity and mechanistic studies on Ru(II) arene complexes with diazadiene ligands. Outstanding performance provided by the introduction of cyclohexyl groups. Profound consequences on the activity by chloride/iodide replacement.